Sir John Hill (1714–1775) and “His” Classification of Fishes: An Example of Eighteenth-Century Plagiarism - Pietsch, Theodore W.; Aili, Hans (Zootaxa, 2023)
John Hill (1714–1775), a brilliant man of many talents, was extremely productive, having produced more than a hundred books and pamphlets on a wide range of subjects, but despised by most contemporaries for his egotistical, argumentative, and provocative manner and for his slanderous writings that resulted in many heated disputes, among scientists and literati alike. Rejected in his attempts to join the Royal Society of London, he began a campaign of criticism and derision against the Society, its president, Martin Folkes (1690–1754), and the Philosophical Transactions, by publishing, under a pseudonym, satires on the Society that destroyed his chances of ever being elected to that body. Accusations of plagiarism followed much of his work. A previously unnoticed example of his wholesale lifting of the classification of fishes published in 1738 by Swedish naturalist Peter Artedi (1705–1735), is described. As for the Royal Society, Hill’s persistent satirization, which was mixed with sound critical advice, is said to have done more to improve the quality of the Philosophical Transactions than any other contemporary effort.